Priorities in The Phasing Design of Rangkasbitung Sub-District Sewerage System - Lani Oktaviani; Ramadhani Yanidar; Lailatus Siami (President University, 2023)
Rangkasbitung Sub-district (105 25’ – 106 30’ EL and 6 18’ – 7 00’ SL) is the capital city of Lebak Regency which has an area of 7,252 Ha. Based on the Master Plan of Lebak Regency 2014 – 2034, It will be built the toll roads and industrial areas in Nameng Village, Citeras Village, and Mekarsari Village. Therefore the Rangkasbitung will become a rapidly growing urban area. The sanitation services are still 60,63%. To achieve the Goal 6 of SDGs, then this paper aims to design an analytical technique the sewerage system in order to achieve sanitation for all, and to recommend the planning phases in order to be effective and efficient sewerage system until the end of the 2040. The Sewerage system design has anticipated the Ciujung River and Ciberang River with seven (7) tributaries that pass through this sub-district. The location of the Waste Water Treatment Plant (WWTP) is designed at a low elevation, namely in Kolelet Wetan, Nameng, and Mekarsari Village by considering the flood-free areas and topography. The recommendations for the construction phases are based on population density and the service area of the WWTP location. The total wastewater discharge is designed as 510.367 L/sec, which will be implemented into two phases. The first phase will build WWTP A = 208.937 L/sec and WWTP B = 275.188 L/sec, then WWTP C = 26.242 L/sec in the second phase. The design of the trunk sewer has a total 24,556 m length, of which 19,043 m will be in the first phase and 5,513 m will be in the second phase. The diameter of the trunk sewer ranges from 300 mm to 1,000 mm. The first phase indicated depth by diameter (d/D) ratio in the range of 55% - 78%, and the velocity range of 0.68 – 2.24 m/sec. The final phase indicated 61% - 75% and the velocity range of 0.69 – 2.24 m/sec.